Application of direct fluorescence-based live/dead staining for assessment of antifungal activity of coconut oil against Candida albicans - Mukhtar, Nor Izzah; Abllah, Zurainie; Shahdan, Intan Azura (2018)
Candida albicans is becoming a significant problem for oral candidiasis worldwide. In addition, the proliferation of antifungal-resistant C. albicans has become a major concern. This study was carried out to evaluate the effects of activated virgin coconut oil (AVCO) and the crude extract of virgin coconut oil (VCO) to search for a new antifungal agent for treatment of oral candidiasis. The viability of C. albicans cells was determined using live/dead bacterial viability kit. C. albicans cells were grown in YPD broth culture overnight. The fungus was treated with AVCO and VCO at concentration of minimum inhibitory concentration (MIC), 6.24 µg/ml. To evaluate the viability of C. albicans cells, SYTO 9 and propidium iodide (PI) staining were used in this study and observed using fluorescence microscopy. C. albicans cells treated with AVCO showed more dead cells compared to cells treated with VCO. The data indicated that exposure of C. albicans to AVCO was the most inhibitory to growth (P<0.01).